Hyperinsulinemia and insulin resistance in the obese may develop as part of a homeostatic response to elevated free fatty acids: a mechanistic case-control and a population-based cohort study - Fryk, Emanuel; Olausson, Josefin; Mossberg, Karin; Strindberg, Lena; Schmelz, Martin; Brogren, Helén; Gan, Li-Ming; Piazza, Silvano; Provenzani, Alessandro; Becattini, Barbara; Lind, Lars; Solinas, Giovanni; et al. (EBioMedicine, 2021)
Background - It is commonly accepted that in obesity free fatty acids (FFA) cause insulin resistance and hyperglycemia, which drives hyperinsulinemia. However, hyperinsulinemia is observed in subjects with normoglycaemia and thus the paradigm above should be reevaluated. - Methods - We describe two studies: MD-Lipolysis, a case control study investigating the mechanisms of obesity-driven insulin resistance by a systemic metabolic analysis, measurements of adipose tissue lipolysis by microdialysis, and adipose tissue genomics; and POEM, a cohort study used for validating differences in circulating metabolites in relation to adiposity and insulin resistance observed in the MD-Lipolysis study. - Findings - In insulin-resistant obese with normal glycaemia from the MD-Lipolysis study, hyperinsulinemia was associated with elevated FFA. Lipolysis, assessed by glycerol release per adipose tissue mass or adipocyte surface, was similar between obese and lean individuals. Adipose tissue from obese subjects showed reduced expression of genes mediating catecholamine-driven lipolysis, lipid storage, and increased expression of genes driving hyperplastic growth. In the POEM study, FFA levels were specifically elevated in obese-overweight subjects with normal fasting glucose and high fasting levels of insulin and C-peptide. - Interpretation - In obese subjects with normal glycaemia elevated circulating levels of FFA at fasting are the major metabolic derangement candidate driving fasting hyperinsulinemia. Elevated FFA in obese with normal glycaemia were better explained by increased fat mass rather than by adipose tissue insulin resistance. These results support the idea that hyperinsulinemia and insulin resistance may develop as part of a homeostatic adaptive response to increased adiposity and FFA. - Funding - Swedish-Research-Council (2016-02660); Diabetesfonden (DIA2017-250; DIA2018-384; DIA2020-564); Novo-Nordisk-Foundation (NNF17OC0027458; NNF19OC0057174); Cancerfonden (CAN2017/472; 200840PjF); Swedish-ALF-agreement (2018-74560).